2018
DOI: 10.1080/10376178.2018.1513809
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early postoperative enteral nutrition versus usual care on serum albumin, prealbumin, transferrin, time to first flatus and postoperative hospital stay for patients with colorectal cancer: A systematic review and meta-analysis

Abstract: EEN can improve nutritional status and promote intestinal function recovery for patients undergoing CRC surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…According to the results of this work, according to a combined analysis of clinical and laboratory data, enteral nutrition comes to the fore in the relative effectiveness of nutritional support, which is confirmed in a number of the literature [7], [10], [15], [16], [17].…”
Section: Discussionsupporting
confidence: 66%
“…According to the results of this work, according to a combined analysis of clinical and laboratory data, enteral nutrition comes to the fore in the relative effectiveness of nutritional support, which is confirmed in a number of the literature [7], [10], [15], [16], [17].…”
Section: Discussionsupporting
confidence: 66%
“…Zhang et al [23] reported that hyperfibrinogenemia is relevant to advanced tumor stages and poor survival in patients with HCC. PA has a short half-life as a predictor of inflammatory stress and nutritional status [24], making it an effective biomarker for morbidity, mortality and tumor progression [25]. Therefore, fibrinogen to prealbumin ratio (FPR), which combines Fib and PA, has been used to predict clinical efficacy and outcome for several types of human cancers [20,26].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence supports the idea that nutritional status is significantly associated with long-term outcomes in cancer patients [39], [40]. As a common nutrition marker, blood PA was found to be related to the 5-year survival rate in patients with malignant tumors such as resected esophageal squamous cell carcinoma and hepatocellular carcinoma [41]- [43].…”
Section: Discussionmentioning
confidence: 89%